2022
DOI: 10.3389/fendo.2022.975912
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal adverse events of metformin treatment in patients with type 2 diabetes mellitus: A systematic review, meta-analysis and meta-regression of randomized controlled trials

Abstract: IntroductionMetformin is the first choice drug in the treatment of type 2 diabetes mellitus but its administration may be linked to gastrointestinal adverse events limiting its use.ObjectivesThe objective of this systematic review and meta-analysis was to assess the risk of gastrointestinal adverse events related to metformin use in patients with type 2 diabetes treated with metformin.MethodsPUB MED/CINAHL/Web of Science/Scopus were searched from database inception until 08.11.2020 for articles in English and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…Additionally, A. muciniphila acts in CNS (Cheng et al, 2021;Higarza et al, 2021;Sun et al, 2022). It is therefore postulated that the reconstruction of the microbiota altered by a metabolic disease under the influence of metformin may be functionally beneficial, but in some patients -especially during the period of increasing the dosage -it may cause gastrointestinal disorders (Nabrdalik et al, 2022). The observed side effects may be related to the effect of the drug on the microbiota (MetaHIT consortium et al, 2015;Elbere et al, 2018, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, A. muciniphila acts in CNS (Cheng et al, 2021;Higarza et al, 2021;Sun et al, 2022). It is therefore postulated that the reconstruction of the microbiota altered by a metabolic disease under the influence of metformin may be functionally beneficial, but in some patients -especially during the period of increasing the dosage -it may cause gastrointestinal disorders (Nabrdalik et al, 2022). The observed side effects may be related to the effect of the drug on the microbiota (MetaHIT consortium et al, 2015;Elbere et al, 2018, 2).…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Similar to our results, Nabrdalik et al stated that compared to other antidiabetic medications, type 2 diabetes patients on metformin have an increased risk of experiencing gastrointestinal side effects including nausea, diarrhea, and stomach pain. [14] Furthermore, Sanchez-Rangel and Inzucchi reported that the most common side effects of metformin are gastrointestinal in nature including nausea, diarrhea, and abdominal discomfort. [15] The most often reported side effects of metformin, according to Rojas et al, were headaches, nausea, vomiting, diarrhea, and stomach pain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, metformin interferes with the normal absorption of bile salts, which contributes to the exacerbation of discomfort and causes additional symptoms, such as loose stools [ 11 ]. A recent meta-analysis showed that using metformin, compared to other antidiabetic drugs, significantly elevates the risk of occurrence of gastrointestinal symptoms—among others, abdominal pain and diarrhoea—and there are some advantages to using an extended-release formulation [ 12 ]. The observed side-effects may be related to the effect of the drug on the microbiota [ 13 ].…”
Section: Metforminmentioning
confidence: 99%